Anti-oppression self-expression: An a/r/tographic understanding of Black and Brown youth's conceptualization(s) of nature - Schmidt, Alayna Mykal (2022)
As the world’s population becomes increasingly urban (United Nations, 2019), there is an urgent need to design cities that facilitate nature connection for youth residents (Cox et al., 2017; Zuniga-Teran et al., 2019), particularly youth of color who experience disproportionate impacts of poor environmental quality and inequitable access to nature due to a history of racist policies in urban design (Jennings et al., 2017; Rigolon, 2016, 2017). Despite historic and current racist policies and experiences in the outdoors, Black and Brown people do access and enjoy nature on their own terms in ways that may not necessarily assimilate into white cultural norms and preferences (Davis, 2018). In an effort to make whiteness, white ideas, and white preferences—which are usually translucent and “normal” in white supremacy culture—opaque, I use nature (with strikethrough) to indicate placing the concept of “nature” under erasure (Derrida, 2016). The ways people conceptualize, understand, and make relationship with/in/about nature drip with emotions and spirituality; our very humanity. These meanings are often hard to explain in words alone, our language falls short of representation. Making and experiencing art can promote non-traditional methods of expression, communication, and meaning-making reverberating into our souls in much the same way as nature can. For these reasons, I used art as a methodology and a method to uncover the meanings and relationships people have with nature at the intersection of racial identity. I sought to understand what nature means for Black and Brown youth in Asheville to ensure that efforts to improve equitable access to nature are the most authentic, relevant, and useful to the people impacted by this work. I used the arts-entangled methodology of a/r/tography (Schultz & Legg, 2019; Springgay et al., 2005) to conduct research in partnership with youth (rather than on) and to decolonize and interrupt extractive and reductive approaches to research. Youth responded to prompts by creating artistic pieces and making brief artist statements about their pieces. My role was “researcher as curator,” organizing the collection and framing youth’s art in Critical Race Theory and Black Feminist Theory. This approach decentered the power I held as a white researcher and attempted to distribute power more equitably to the Black and Brown youth co-researchers. Additionally, I kept a personal reflexive journal in which I responded to my own prompts related to how my social identity influences my conceptualization of nature and my approach to environmental education as a white artist/researcher/teacher. Using Creative Analytic Practice (CAP) (Parry & Johnson, 2007), I represented the results and discussion of this research as an art zine which challenges viewers to consider how the viewer’s own social identities influence how they conceptualize nature and invites the broader community to participate in creating art around what nature means.